2018
DOI: 10.1007/s12291-018-0740-3
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effect of IL-6 -174 G/C Polymorphism and Promoter Methylation in the Risk of Coronary Artery Disease Among South Indians

Abstract: Inflammation plays an important role in the pathogenesis of atherosclerosis and coronary syndromes; moreover, various lines of evidence suggest that genetic factors do contribute to the risk of coronary artery disease (CAD). The proinflammatory cytokine IL-6 is a central mediator of inflammation associated with CAD. The present study is aimed to investigate the association of single nucleotide polymorphism in the promoter region of the IL-6 gene (-174 G [ C) and methylation with the susceptibility of CAD. Geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“… India 2014 65±5 64±6 200 200 12 Gao, Y. L. [ 38 ] China 2016 61.50±10.53 52.54±10.65 275 286 13 Ghazouani, Lakhdar [ 39 ] Tunisia 2010 58.1±12.0 56.7±14.1 418 406 14 Humphries, S. E [ 40 ]. England 2001 56·7±3·6 56·0±3·4 162 2589 15 Indumathi, B [ 41 ]. India 2019 56.00 ± 12.00 265 205 16 Jabir, N. R [ 42 ] Saudi Arabia 2017 60.6±8.85 47.7±5.06 90 89 17 Jia, X. W [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“… India 2014 65±5 64±6 200 200 12 Gao, Y. L. [ 38 ] China 2016 61.50±10.53 52.54±10.65 275 286 13 Ghazouani, Lakhdar [ 39 ] Tunisia 2010 58.1±12.0 56.7±14.1 418 406 14 Humphries, S. E [ 40 ]. England 2001 56·7±3·6 56·0±3·4 162 2589 15 Indumathi, B [ 41 ]. India 2019 56.00 ± 12.00 265 205 16 Jabir, N. R [ 42 ] Saudi Arabia 2017 60.6±8.85 47.7±5.06 90 89 17 Jia, X. W [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous published studies took promoters as key differentially methylated regions in CAD, while other intragenic regions were less concerned (Heidari et al, 2019;Indumathi et al, 2019). Recently, a few studies have demonstrated methylation sites in the gene body or TSS1500 were also essential to the pathogenesis of CAD (Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous published studies took promoters as key differentially methylated regions in CAD, while other intragenic regions were less concerned [26,27]. Recently, a few studies have demonstrated methylation sites in gene body or TSS1500 were also essential to the pathogenesis of CAD [28].…”
Section: Discussionmentioning
confidence: 99%